2009
DOI: 10.1105/tpc.109.073239
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Regulate Lateral Root Formation inPopulusthrough Interactions with Auxin and Other Hormones  

Abstract: The role of gibberellins (GAs) in regulation of lateral root development is poorly understood. We show that GA-deficient (35S:PcGA2ox1) and GA-insensitive (35S:rgl1) transgenic Populus exhibited increased lateral root proliferation and elongation under in vitro and greenhouse conditions, and these effects were reversed by exogenous GA treatment. In addition, RNA interference suppression of two poplar GA 2-oxidases predominantly expressed in roots also decreased lateral root formation. GAs negatively affected l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
181
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 94 publications
(121 reference statements)
8
181
0
Order By: Relevance
“…One of the major outcomes of this study, consistent with our previous work under in vitro conditions and Atgai Native Native 10-2, 102-2, 115, 117 GAI-X-1, GAI-X-2, GAI-X-3, GAI-X-4 Arabidopsis Control 717-1 Control early greenhouse growth (Gou et al, 2010(Gou et al, , 2011, is that root biomass fraction was enhanced in semidwarf trees. Both in the raised-bed environment, where we could most fully harvest and thus more accurately measure woody root biomass, and in the field site, the transgenics showed a higher fraction of root biomass.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…One of the major outcomes of this study, consistent with our previous work under in vitro conditions and Atgai Native Native 10-2, 102-2, 115, 117 GAI-X-1, GAI-X-2, GAI-X-3, GAI-X-4 Arabidopsis Control 717-1 Control early greenhouse growth (Gou et al, 2010(Gou et al, , 2011, is that root biomass fraction was enhanced in semidwarf trees. Both in the raised-bed environment, where we could most fully harvest and thus more accurately measure woody root biomass, and in the field site, the transgenics showed a higher fraction of root biomass.…”
Section: Discussionsupporting
confidence: 79%
“…(Evans and Fischer, 1999). Thus, although reduced stature of fruit, ornamental, and street trees has clear value, and it is possible that semidwarf trees could also have specialized uses such as for bioremediation, stress tolerance, or carbon sequestration (Ragauskas et al, 2006) as a result of their increased allocation to root growth (Busov et al, 2006;Gou et al, 2010), it is unclear whether semidwarfism could be beneficial in promoting wood yield in dense plantings. It was also unclear whether semidwarfism observed in open grown trees would also obtain in mixed plantings, as trees compensate strongly to favor height over stem growth under competition for light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological functions of GA in root growth have been discussed for Arabidopsis (Tanimoto 2012;Mauriat et al 2014) and crosstalk between indole-3-acetic acid (IAA) and GA has been demonstrated in the signaling system (Fu and Harberd 2003;Gou et al 2010). Supplementation of GA 3 was reported to induce increases in secondary metabolite production and also affected cell viability and root morphogenesis of E. purpurea in hairy root cultures (Abbasi et al 2012).…”
Section: In Vitro Plantlet Regenerationmentioning
confidence: 99%